Association Between Gut Dysbiosis and Sepsis-Induced Myocardial Dysfunction in Patients With Sepsis or Septic Shock - Chen, Yu; Zhang, Fu; Ye, Xin; Hu, Jing-Juan; Yang, Xiao; Yao, Lin; Zhao, Bing-Cheng; Deng, Fan; Liu, Ke-Xuan (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Sepsis-induced myocardial dysfunction (SIMD) seriously affects the evolution and prognosis of the sepsis patient. The gut microbiota has been confirmed to play an important role in sepsis or cardiovascular diseases, but the changes and roles of the gut microbiota in SIMD have not been reported yet. This study aims to assess the compositions of the gut microbiota in sepsis or septic patients with or without myocardial injury and to find the relationship between the gut microbiota and SIMD. Methods The prospective, observational, and 1:1 matched case–control study was conducted to observe gut microbiota profiles from patients with SIMD (n = 18) and matched non-SIMD (NSIMD) patients (n = 18) by 16S rRNA gene sequencing. Then the relationship between the relative abundance of microbial taxa and clinical indicators and clinical outcomes related to SIMD was analyzed. The receiver operating characteristic (ROC) curves were used to evaluate the predictive efficiencies of the varied gut microbiota to SIMD. Results SIMD was associated with poor outcomes in sepsis patients. The beta-diversity of the gut microbiota was significantly different between the SIMD patients and NSIMD subjects. The gut microbiota profiles in different levels significantly differed between the two groups. Additionally, the abundance of some microbes (Klebsiella variicola, Enterobacteriaceae, and Bacteroides vulgatus) was correlated with clinical indicators and clinical outcomes. Notably, ROC analysis indicated that K. variicola may be a potential biomarker of SIMD. Conclusion Our study indicates that SIMD patients may have a particular gut microbiota signature and that the gut microbiota might be a potential diagnostic marker for evaluating the risk of developing SIMD.